Retrospective analysis of 17 patients with mitochondrial membrane protein-associated neurodegeneration diagnosed in Russia. (March 2021) - Sparber, Peter; Krylova, Tatiana; Repina, Svetlana; Demina, Nina; Rudenskaya, Galina; Sharkova, Inna; Sharkov, Artem; Kadyshev, Vitaly; Kanivets, Ilya; Korostelev, Sergey; Pomerantseva, Ekaterina; Kaimonov, Vladimir; et al.
Abstract: Introduction: Mitochondrial membrane protein-associated neurodegeneration (MPAN) is a rare neurological syndrome caused by pathogenic variants in the C19orf12 and is characterized by iron deposition in the basal ganglia and substantia nigra. Only a limited number of cohort studies were published to date and the prevalence of MPAN remains uncertain. Methods: Recruited subjects with MPAN in Russia were diagnosed by whole-exome sequencing or Sanger sequencing of the C19orf12 gene. Data of over 14000 whole exome sequencing analyses was used to calculate the estimated disease frequency. RNA analysis was performed by RT-PCR. QSVanalyzer software was used to quantify the allelic disbalance. Results: We describe the clinical and molecular characterizations of 17 patients with MPAN. DNA analysis detected three previously undescribed pathogenic/likely pathogenic variants in the C19orf12 gene. The estimated disease frequency was calculated to be 1:619150. We describe unusual clinical observations in several cases. One patient showed severe neurogenic muscle weakness along with a lack of marked spasticity or optic nerve atrophy. In another mild clinical case with the NM_001031726.3:c.204_214del (p.(Gly69Argfs*10)) variant in a heterozygous state, a marked allelic disbalance was observed on the RNA level with reduced expression level of the wild-type allele. Thus, this case became the first one of a possible regulatory variant causing MPAN. Conclusion: We reported a detailed clinical and molecular characterization of the third-largest MPAN cohort. We expanded the mutational and clinical spectrum of MPAN. Moreover, we calculated the estimated MPAN frequency in the Russian population for the first time. Highlights: We report the third-largest cohort of patients with Mitochondrial Membrane Protein-Associated Neurodegeneration (MPAN). Three novel pathogenic variants along with unusual clinical presentations are described. The estimated disease frequency of MPAN in the Russian population was calculated for the first time. Elevated creatine kinase levels were found in the majority of patients.